2021
DOI: 10.51248/.v41i4.908
|View full text |Cite
|
Sign up to set email alerts
|

Does serum Vitamin D affect lipid profile?

Abstract: Introduction and Aim: Vitamin D, besides its classical physiological functions, exerts effects on brain, prostate, breast, colon, pancreas, and immune cells due to the ubiquitous presence of its receptors. Hypovitaminosis D predisposes individuals to various micro and macro vascular complications of metabolic syndrome and diabetes mellitus. Despite speculations regarding implications of its deficiency on the cardio metabolic health of general/ susceptible population, its role remains underexplored in the India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Vitamin D may also prevent cardiovascular disease by regulating several genes involved in cell differentiation, proliferation, apoptosis, and angiogenesis [72]. In fact, another proposed mechanism for the protective effect of vitamin D on CVD is the control of lipid parameters [11,12,33,[73][74][75][76] In the present study, lipid profile assessment revealed dyslipidemia in 33.3% of all participants. Non-parametric regression showed that 25(OH)D concentration was inversely associated with TC, TG, and LDL-C levels and positively associated with HDL-C.…”
Section: Discussionmentioning
confidence: 60%
“…Vitamin D may also prevent cardiovascular disease by regulating several genes involved in cell differentiation, proliferation, apoptosis, and angiogenesis [72]. In fact, another proposed mechanism for the protective effect of vitamin D on CVD is the control of lipid parameters [11,12,33,[73][74][75][76] In the present study, lipid profile assessment revealed dyslipidemia in 33.3% of all participants. Non-parametric regression showed that 25(OH)D concentration was inversely associated with TC, TG, and LDL-C levels and positively associated with HDL-C.…”
Section: Discussionmentioning
confidence: 60%